Energy expenditure on ground cutting by continuous action buckets to form the underlying layer of the road - V. A. Nikolaev (Вестник СибАДИ)
Introduction. To solve the problem of accelerating the construction of roads, improving their quality, it is advisable to use a continuous action unit to form a underlying layer. In general, energy costs for the construction of roads are a significant share occupied by work aimed at cutting and transporting the ground. The working bodies of existing technical means carry out mainly energy-intensive cutting of the ground, which theoretically can be likened to cutting a punch. The energy costs of ground cutting can be significantly reduced by the use of blade cutting. In the bucket of the continuous action unit to form a underlying layer of roads provides the use of working bodies, cutting the ground with blades of knives. The process of filling the bucket with cut soil, the forces attached to the bucket, and the total amount of energy spent on cutting the ground with the buckets of the continuous action unit to form the underlying layer are considered. The method of research. The method of constructions to detect the kinematics of filling the bucket with the cut ground is given. The method of calculation is given: the path of the ground on the bottom of the bucket case when it is filled; the resulting force of force projections in the longitudinal-vertical, cross-vertical and horizontal plane attached to the bucket; moments attached to the bucket in a longitudinal-vertical and horizontal plane, when the bucket is empty and full. The formulas for calculating the total energy on the movement of the bucket when cutting the ground without taking into account the energy costs of the cutting process and determining the total energy costs of cutting the ground by one cubic meter of continuous action buckets to form the underlying layer of roads are given. Results. On the basis of the developed method, the conditional path of the ground along the bottom of the bucket case was calculated, the resulting forces of force projections in the longitudinal-vertical, cross-vertical and horizontal plane attached to the bucket were revealed. The moments attached to the bucket in the longitudinal-vertical and horizontal plane, when the bucket is empty and full, have been determined. The total energy for moving the bucket during ground cutting is calculated without taking into account the energy costs of the cutting process. The total energy costs of cutting the ground by one cubic meter of continuous action buckets to form the underlying layer of roads have been determined. Conclusion. During the filling of the bucket of the unit of continuous action to form the underlying layer of roads cut off soil is twisted and shift of the cut-off layer, which contribute to its destruction into fragments. In a cross-vertical plane, the bucket is balanced. The moment attached to the bucket in the longitudinal-vertical plane is balanced by elements of the structure of the unit. The total energy on moving the bucket when cutting the ground, without taking into account the energy costs of the cutting process, includes energy costs: to accelerate the ground with a bucket, to overcome the friction of the bottom plane of the bucket on the ground, to the additional horizontal force to move the bucket, caused by friction in the elements of the structure. It is u_k≈13 kJ/m3. Theoretically reasonable total energy costs for ground cutting of one cubic meter by the buckets of the continuous action unit to form the underlying layer of roads〖u 〗 (k-gr) ≈109 kJ/m.